Using social media in the elderly group for promoting physical exercise - สุทธิรักษ์ วโรชา (Siam Communication Review, 2020)
In the year 2021, Thailand will enter "Complete aged society” the population of ages 60 years and older account for 20 percent of the total population. Important problems that elderlies face are about health issues caused by many changes in the body that affect the system of various organs that are clearly observed, such as a decrease in tolerance, agility, and strength. Elderlies who do not rehabilitate to improve their health will experience chronic illness that causes physical fitness to be lower than it should be, so it is important to encourage exercise. For the elderly to live longer with quality exercise, activities will vary according to the health and ability of each elderly person. There are many ways to improve elderly’s health, such as walking or running slowly, exercise, swimming and water exercises, riding a bicycle and dancing. Social media today is an important channel used to transmit information about exercise in many aspects, especially health knowledge, in order to distribute the correct information. The most popular social media used by the elderly is Line, followed by YouTube and Facebook. The use of social media is both positive and negative. The positive way is to develop relationships and find new friends and engage in participation and exchange of opinions on various matters. At the same time, it can also create a negative impact, including the spread of unreliable and false information. Elderlies prefer to share health information that may be convincing but not necessarily reliable, which can have negative impact. Therefore, when using social media, the elder needs to have knowledge and analytical skills. The information received must have a goal to use and be used properly. There should be an agency responsible for developing programs to increase knowledge and recommend the use of social media, for all seniors to be able to use media to recognize useful information. There should be a main unit to recommend content producers to make clips on exercise and health care that are diverse, appropriate, and reliable.